The mesenteric defects in laparoscopic Roux-en-Y gastric bypass: 5 years follow-up of non-closure versus closure using the stapler technique - Aghajani, Ebrahim (Surg Endosc, 2017)
BACKGROUND: Internal hernia (IH) is a common complication of laparoscopic Roux-en-Y gastric bypass (LRYGB). Little large-volume data exist on how to handle the mesenteric defects during LRYGB. This study evaluated long-term follow-up (5.5 years) of 2443 patients with primary closure of the mesenteric defects with a stapling device at LRYGB, in comparison with a non-closed group from the same centre. METHODS: All patients (N = 4013) undergoing LRYGB over a 10-year period (2005–2015) at a single institution were evaluated. The mesenteric defects were routinely closed starting June 2010. In total, 1570 non-closure patients and 2443 patients with stapled closure of the defects were prospectively entered and the results analysed. RESULTS: Closure of the mesenteric defects increased surgical time by 4 min and did not affect the 30-day complication rate. IH incidence was significantly lower (2.5%) in the closure group compared with 11.7% in the non-closure group, at 60 months. The relative risk reduction by closing the mesenteric defects was 4.09-fold (95% CI = 2.97–5.62) as calculated using a survival model. CONCLUSIONS: Internal hernia after LRYGB occurs frequently if mesenteric defects are left unclosed. Primary closure with a hernia-stapling device is safe and significantly reduces the risk of internal hernia. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00464-017-5415-2) contains supplementary material, which is available to authorized users.